2019
DOI: 10.7150/ijbs.29599
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, Nonalcoholic Fatty Liver Disease and Adipocytokines Network in Promotion of Cancer

Abstract: Western populations are becoming increasingly sedentary and the incidence of nonalcoholic fatty liver disease (NAFLD) is increasing and becoming one of the most common causes of liver disease worldwide. Also, NAFLD is considered one the new emerging risk factors for development of tumors of the gastro-intestinal tract, particularly hepatocellular carcinoma (HCC). Visceral obesity is an important risk factor for the onset of NAFLD. An accumulation of ectopic fat, including visceral obesity and fatty liver leads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
84
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(95 citation statements)
references
References 64 publications
5
84
0
Order By: Relevance
“…The prevalence of NAFLD is about 50-90% in obese subjects. 19 The pooled prevalence of NAFLD in patients with T2DM is 59.67% (95% confidence interval (CI): 54.31-64.92%) according to a meta-analysis of 24 studies. 20 The growing epidemic of obesity and T2DM have fueled an increasing prevalence of NAFLD worldwide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of NAFLD is about 50-90% in obese subjects. 19 The pooled prevalence of NAFLD in patients with T2DM is 59.67% (95% confidence interval (CI): 54.31-64.92%) according to a meta-analysis of 24 studies. 20 The growing epidemic of obesity and T2DM have fueled an increasing prevalence of NAFLD worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…20 The growing epidemic of obesity and T2DM have fueled an increasing prevalence of NAFLD worldwide. [19][20][21][22][23] Moreover, obesity and T2DM also increase the risk of NAFLD progression to NASH, cirrhosis, and HCC. 22,23 In Asia, NAFLD can occur in lean subjects with central obesity, which may be partly because of a higher metabolic activity of visceral fat and genetic predisposition, such as the patatin-like phospholipase domain-containing 3 (PNPLA3) polymorphism.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of constant metabolic activity and regular exposure to proinflammatory factors contributes to the state of chronic low-level inflammation of this organ [12]. Disruptions of this close immuno-metabolic interaction are associated with pathological inflammation that can lead to liver fibrosis, cancer, non-alcoholic fatty liver disease (NAFLD), obesity and other chronic diseases [207][208][209][210].…”
Section: Livermentioning
confidence: 99%
“…75 NAFLD represents a new emerging risk factor for the onset of liver and extra-hepatic carcinogenesis, characterized by impaired production of adipocytokines which, in turn, favor an increase in pro-inflammatory cytokines, further contributing to the microenvironment favorable to the development of cancer. 76 Data from the Surveillance, Epidemiology and End Results-Medicare linked database between 2004 and 2009 showed that NAFLD represented the third most common cause of HCC, after hepatitis C and alcohol-related disease diagnosed in 14.1% of the patients with HCC. 77 However, to date, the prevalence of NAFLD in the general population is increasing especially in developed countries.…”
Section: The Role Of Iron Overloadmentioning
confidence: 99%